Autism-Friendly Schools: Including the Voices of Autistic Students in Primary and Post-Primary Education in Ireland. - Lynam, Aoife (Dublin City University, 2025)
Autism is a lifelong developmental disability or difference which relates to how a person communicates and interacts with others, and how they experience the world around them (AsIAm, 2025). Under Article 24 of the United Nations Convention on the Rights of Persons with Disabilities, autistic1 children have the right to be fully included in mainstream educational settings, with individualised supports and accommodations in place to maximise their academic and social development at school (United Nations, 2006). Despite this, many autistic children continue to experience exclusion and barriers to inclusive education which can result in lifelong difficulties. Notably, the views and experiences of autistic children and young people are not currently included in the development of educational policy and practices for them. Inclusion in education refers to the process of identifying and removing barriers to the presence, participation and achievement of all students (Ainscow et al., 2006). This study aimed to undertake the first systematic investigation of the experiences of autistic students in primary and post-primary schools, in both mainstream and special school provision, in Ireland to create new knowledge that would lead to clearly implementable supports for inclusive education policy and practice in Ireland. This study also aimed to examine the wider school community’s understanding of autism, and attitudes to inclusion, to provide an evidence base for educational policies and guide inclusive education practices.
PUBLISHED
Keywords: Inclusive Society; Inclusive Education; Autistic Spectrum disorders